MENGUKUR INKLUSI KEUANGAN DIGITAL PADA UMKM DENGAN MODIFIKASI MOBILE TECHNOLOGY ACCEPTANCE MODEL - Permana, Gusi Putu Lestara; Putri, Ni Kadek Arisya (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) have demonstrated resilience and played a crucial role in saving Indonesia's economy during significant crises, such as the Covid-19 pandemic. Technology, especially in finance, can drive digital financial inclusion for MSMEs despite challenges. This study assesses digital financial inclusion in MSMEs through Payment Gateway, applying a modified Mobile Technology Acceptance Model (MTAM). Using purposive sampling, 100 MSME operators were surveyed, and data was analyzed with PLS-SEM. The findings highlight service usefulness, ease of use, intention, cost, and usage intensity significantly affecting Payment Gateway adoption in Denpasar's MSMEs. The study's implications suggest that MTAM offers valuable insights into the factors influencing Payment Gateway adoption, providing a basis for government and financial institutions to design programs supporting digital payment adoption and enhancing financial inclusion within MSMEs.